En användarstudie med konceptframtagning av ögonskydd för arbetare inom byggbranschen - Ohlén, Sandra; Wellander, Hanna (My University, 2020)
When working in the construction business, using personal protective equipment is a part of the daily routine. Its purpose is to prevent the workers from external damage while performing their work assignments. But despite that, studies show that workers within the construction business experience high risk for injuries. It is also shown that 47% does not use their personal protective equipment, which can be affected by uncomfortable fitting or that it does not combine well with other protective gear. Therefore, the purpose of this bachelor thesis is to choose one type of personal protective equipment and gain a deeper understanding regarding the usage and potential improvements of the product. The project begun with a user study consisting of observations, a survey and interviews that were performed at different construction companies. This was done to understand the current situation regarding personal protective equipment and to map out the different types of problems that the workers experienced. After this, the decision of which personal protective equipment that should be in focus was made, which resulted in protective eyewear. The data from the used methods were later analyzed in order to understand the problems with the chosen product, which led to a list of functions and a list of specifications. Based on the user study, multiple ideas were created using the method 6-3-5 within each problem area. Favourites from each problem area were combined in a morphological matrix which led to several ideas. These were discussed and gave three concepts which were evaluated and resulted in one winning concept. This concept was developed further and eventually led to our final concept Induco. Induco is a safety eyewear developed like a hybrid between a visor and spectacles. It is placed on the inside of the helmet and has exchangeable lenses.
Keywords: Personal protective equipment; Product development, Safety eyewear, User study